2003
DOI: 10.1111/1469-8986.00076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial and natural baroreceptor stimulation on nociceptive responding and pain

Abstract: The arterial baroreflex may mediate hypertensive hypoalgesia. Carotid baroreceptors can be artificially stimulated by neck suction and inhibited by compression. Effects of brief neck suction and compression on nociceptive responding and pain were studied in 25 normotensive adults. The sural nerve was electrocutaneously stimulated at threshold intensity during systole or diastole combined with neck suction, neck compression, or no pressure. Nociceptive responding was indexed by electromyographic activity elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
68
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 40 publications
14
68
0
Order By: Relevance
“…Specifically, the NFR was facilitated by the distracting and arousing computer game task, Tetris ® , while pain was attenuated. Such a dissociation between pain and the NFR has been noted previously (e.g., Andersen et al, 1995;Bouhassira et al, 2003;Edwards et al, 2001Edwards et al, ,2002Edwards et al, ,2003aEdwards et al, ,2006McIntyre et al, 2006;Terkelsen et al, 2004;Willer et al, 1979). In addition, a similar dissociation has been recently reported between pain and the nociceptive blink reflex during psychological arousal (Koh and Drummond, 2006).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Specifically, the NFR was facilitated by the distracting and arousing computer game task, Tetris ® , while pain was attenuated. Such a dissociation between pain and the NFR has been noted previously (e.g., Andersen et al, 1995;Bouhassira et al, 2003;Edwards et al, 2001Edwards et al, ,2002Edwards et al, ,2003aEdwards et al, ,2006McIntyre et al, 2006;Terkelsen et al, 2004;Willer et al, 1979). In addition, a similar dissociation has been recently reported between pain and the nociceptive blink reflex during psychological arousal (Koh and Drummond, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…In humans, the evidence in favour of opioid dysfunction is mostly negative (e.g., Bruehl et al, 2002;France et al, 2005;Ring et al, 2007;Schobel et al, 1998;cf. McCubbin and Bruehl, 1994;McCubbin et al, 2006) whereas the evidence for baroreceptor activation is more mixed (e.g., al 'Absi et al, 2005;Edwards et al, 2001Edwards et al, ,2003aGuasti, Zanotta, Mainardi, et al, 2002;McIntyre et al, 2006;Rau et al, 1995). Although the current experiments were designed to investigate the function of the descending pain modulation systems in essential hypertension and risk for hypertension, results indicated that there were no differential effects on nociception or pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In concordance with this, previous research has found links between baroreflex sensitivity and the hypertension-hypoalagesia phenomenon. [36][37][38] For example, cardiac cycle synchronized acute baroreceptor stimulation 37 and natural activation of baroreceptors 36 produced decreased pain perception in humans. However, it is also possible that other mechanisms, possibly in conjunction with baroreflex dysregulation, may play a role in the blood pressure-pain relationship.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pain catastrophizing is associated with elevated negative affect (Hirsh et al 2007), which in turn is often associated with heightened cardiovascular stress reactivity (Burns 1995;Feldman et al 1999;Kamarck et al 1998;Prkachin et al 1999). Prior work indicates that elevations in systolic blood pressure trigger endogenous analgesic mechanisms through functional links between the cardiovascular and pain regulatory systems (e.g., Bruehl and Chung 2004;Edwards et al 2001Edwards et al , 2003Ghione 1996;Rau and Elbert 2001). In this context, a mediation model would predict that catastrophizing would be associated with lower pain intensity through activation of blood pressure-related analgesia.…”
mentioning
confidence: 99%